Pengaruh Food Quality, Price, Service Quality dan Perceived Value terhadap Customer Loyality pada Restoran Aneka Rasa Jambi dengan Customer Satisfaction sebagai Variabel Intervening - Novita Sari; Ade Perdana Siregar (J-MAS (Jurnal Manajemen dan Sains), 2019)
Indonesia is the fourth most populous country in the world, after China, India and the United States, with a population of 2018 of around 267 million. The increase in the average population will be a major contributor to the growth of the food and beverage industry. Today's mobility of people is getting higher so it consumes food outside the home. Restaurant products are determined by five factors, namely food and beverage factors, service factors, hygiene and hygiene factors, price factors and atmospheric factors, whereas based on the activities and food or drinks served, restaurants are classified into twenty types ranging from A'la carte restaurant to main dining room. The objectives of this study are: (1) to analyze the effect of food quality, price, service quality and partial perceived value on customer satisfaction; (2) partially analyze the influence of food quality, price, service quality and perceived value on customer loyalty; (3) analyze customer satisfaction mediation due to the influence of food quality, price, service quality and perceived value on customer loyalty. The sample was determined using the Slovin formula of 100 respondents. Survey method with descriptive and quantitative analysis. The analytical tool used in this study is the smartpls application version 3.0. The results of the study note that food quality, price, service quality and perceived value affect customer satisfaction, food quality, price, service quality and perceived value affect customer loyalty and customer satisfaction can mediate the relationship between food quality, price, service quality and perceived value towards customer loyalty.